2015
DOI: 10.1155/2015/913424
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Ligand Complexes ofN-Methyl-N-phenyl Dithiocarbamate: Synthesis, Characterisation, Antifungal Activity, and Solvent Extraction Studies of the Ligand

Abstract: A series of mixed ligand dithiocarbamate complexes with a general formula [ML2(py)2], where M = Mn(II), Co(II), Ni(II), and Cu(II), py = pyridine, and L = N-methyl-N-phenyl dithiocarbamate have been prepared and characterised by elemental analysis, FTIR and Uv spectroscopy, magnetic moment, and thermogravimetric and conductance analysis. The infrared spectra showed that symmetrical bidentate coordination occurred with the dithiocarbamate moiety through the sulfur atoms, while neutral monodentate coordination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…In the present study, the complexes (II and V) show small band at 1624 and 1631 cm -1 , respectively. Other bands are masked by those of dithiocarbamate ligand [26]. A new band appears in spectra of compounds (II and V) at 444 and 470cm -1 , respectively, due to (M-N) stretching mode, which matches well with the literature values [27].…”
Section: Infrared Spectroscopysupporting
confidence: 87%
“…In the present study, the complexes (II and V) show small band at 1624 and 1631 cm -1 , respectively. Other bands are masked by those of dithiocarbamate ligand [26]. A new band appears in spectra of compounds (II and V) at 444 and 470cm -1 , respectively, due to (M-N) stretching mode, which matches well with the literature values [27].…”
Section: Infrared Spectroscopysupporting
confidence: 87%
“…The spectral measurements were carried out at Faculty of Science, Benha University. Magnetic susceptibility measurements were carried out by Gouy method using Hg[Co(CN) 4 ] as calibrant and magnetic susceptibility Johnson Matthey balance. The effective magnetic moments were calculated using the relation µ eff .=2.828 (X m T) 1/2 BM where Ӽ m is the molar susceptibility corrected for diamagnetism and T is the absolute temperature.…”
Section: Physical Measurementsmentioning
confidence: 99%
“…The early discovered Cis-platin was regarded as one of the most effective anticancer drugs, even if severe toxicities and drug resistance phenomena limit its clinical use. Therefore, in recent years there has been a rapid expansion in research and development of novel metalbased biologically active and anticancer complexes [2][3][4]. Numerous mixed ligands transition metal complexes have been investigated by various techniques and their biological activities were extensively studied [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The selectivity index as high as 32 and 64, which indicates the fact that these compounds could be used as good anticancer agents [25]. Ekennia et al [26] prepared a novel N-methyl-N-phenyl dithiocarbamate and its Ni(II), Co(II), Cu(II) and Mn(II) complexes (Schemes IV and V). The structures of ligand and their metal complexes had been resolved, the ligand acts as a bidentate and coordinated with metal via sulfur atoms of dithiocarbamate and through the nitrogen atom of pyridine.…”
mentioning
confidence: 99%
“…Ekennia et al [26] synthesized bis(N-methyl-N-phenyl dithiocarbamate) and its metal complexes, having the general formula [M{S2CN(MePh)}2] (where M = Cu, Co and Ni) ( Similarly, Osoro et al [34] reported the synthesis and characterization of piperazinedithiocarbamate (pipdtc) bridged homobinuclear mixed ligand complexes of Mn(II) containing chelated amino acidato ligands viz., glycine, alanine, phenyl alanine, tyrosine, methionine and cystine. The complexes were screened for antimicrobial activity which showed the promising results against the common bacteria and fungi studied.…”
mentioning
confidence: 99%